THE INFLUENCE OF SKEPTICISM, INDEPENDENCE, AND MOTIVATION ON AUDIT QUALITY AT THE FINANCIAL AND DEVELOPMENT SUPERVISION AGENCY (BPKP) OF NORTH SUMATRA PROVINCE - Hutagalung, Geby Tarina; Deliana, Deliana; Surianti, Meily; Simanjuntak, Darmawati; Rahman, Abdul; Syahputra, Rizki (UPT Publikasi Ilmiah UNISBA, 2024)
The research aims to empirically prove the influence of skepticism, independence and motivation on audit quality at the Financial and Development Supervisory Agency (BPKP) of North Sumatra Province. The data collection technique uses a questionnaire distributed to auditors via Google Forms. Data analysis employs quantitative methods with statistical tools, specifically using Smart Partial Least Squares software. The test results show that skepticism and motivation significantly effect audit quality, while independence does not. The study identifies several limitations, suggesting that future research should include additional variables to explore factors influencing audit quality and expand the population and sample size for further investigation. Keywords : Audit Quality, Independence, Motivation, Skepticism